2012
DOI: 10.1113/jphysiol.2011.211920
|View full text |Cite
|
Sign up to set email alerts
|

Umami taste in mice uses multiple receptors and transduction pathways

Abstract: Non-technical summary The distinctive umami taste elicited by L-glutamate and some other amino acids is thought to be initiated by G-protein-coupled receptors, such as heteromers of taste receptor type 1, members 1 and 3, and metabotropic glutamate receptors 1 and 4. We demonstrate the existence of multiple types of glutamate-sensitive gustatory nerve fibres and the contribution of multiple receptors and transduction pathways to umami taste. Such multiple systems for umami taste may differentially contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
88
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 59 publications
7
88
3
Order By: Relevance
“…It has been suggested that there are multiple receptors for amino acid sensing in the lingual epithelium (67). It is likely that a similar situation may exist in the gut.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that there are multiple receptors for amino acid sensing in the lingual epithelium (67). It is likely that a similar situation may exist in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Among the proposed lingual and/or intestinal epithelial amino acid receptors, T1R1-T1R3, mGluR4, mGluR1, and CaSR, only T1R1 contains all four critical residues required for IMP/GMP binding. Therefore, signal transduction in response to amino acids by other receptors cannot be enhanced by addition of these nucleotide monophosphate esters (67,70).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in mammals other candidates for the umami taste include taste-specific variants or isoforms of metabotropic glutamate receptors (mGluRs) such as mGluR1 and mGluR4, which are members of another class of GPCRs, binding L-glutamic acid (Yasumatsu et al, 2012).…”
Section: Taste Receptorsmentioning
confidence: 99%
“…Therefore, the response of neurons that seemingly are most strongly activated by MSG might merely reflect their sensitivity to other components than glutamate. It should be noted that a recent report showed the existence of S-best and MPG-best mouse CT fibers, each of which can be further divided into two subcategories that do or do not possess a synergistic response to an umami stimulus mixture (Yasumatsu et al 2011). Some mouse single fungiform taste cells are also known to respond best and specifically to MSG (Yoshida et al 2009).…”
Section: Discussionmentioning
confidence: 99%